Prograded foredunes of Western Australia's macro‐tidal coast – implications for Holocene sea‐level change and high‐energy wave impacts. Issue 6 (14th November 2014) - Engel, Max; May, Simon Matthias; Scheffers, Anja; Squire, Peter; Pint, Anna; Kelletat, Dieter; Brückner, Helmut
Abstract The Holocene evolution of the Canning Coast of Western Australia has largely been overlooked so far mainly due to its remoteness and low population density. We report on new data from a sequence of foredunes inside the macro‐tidal Admiral Bay, 110 km southwest of Broome. Based on sediment cores, differential global positioning system (dGPS)‐based elevation transects, and stratigraphical analyses on outcrops of the relict foredunes, we aim at reconstructing Holocene coastal changes and relative sea levels (RSLs), as well as identifying and dating imprints of extreme‐wave events. Sedimentary analyses comprise the documentation of bedding structures, foraminiferal content and macrofaunal remains, grain size distribution, and organic matter. The chronological framework is based on 26 carbon‐14 accelerator mass spectrometry (14C‐AMS) datings. Marine flooding of the pre‐Holocene surface landward of the 2.5 km‐wide foredune barriers occurred 7400–7200 cal bp, when mangroves colonized the area. After only 200–400 years, a high‐energy inter‐tidal environment established and prevailed until c. 4000 cal bp, before turning into the present supralittoral mudflat. During that time, coastal regression led to beach progradation and the formation of aligned foredunes. Drivers of progradation were a stable RSL or gradual RSL fall after the mid‐Holocene and a positive sand budget. The foredunes overlie upper beach deposits located up to >2 m above the present upper beach level and provide evidence for a higher mid‐Holocene RSL. Discontinuous layers of coarse shells and sand are intercalated in the foredunes, indicating massive coastal flooding events. One such layer was traced over three dune ridges and dated to c. 1700–1550 cal bp. However, it seems that most tropical cyclones induce net erosion rather than deposition at aligned foredunes and thus, they are only suitable for reconstructing temporal variability if erosional features or sedimentation reliably tied to these events can be identified and dated accurately. Copyright © 2014 John Wiley & Sons, Ltd.